Political legitimacy in Asia : new leadership challenges - Kane, John; Loy, Hui-Chieh; Patapan, Haig; SpringerLink (Online service) (New York : Palgrave Macmillan US, 2011)
This book explores the challenges and obstacles faced by dissident leaders in Asia seeking to introduce reforms into regimes that are either imperfectly democratic or frankly hostile to democratic practices and institutions.
Keywords: Culture -- Study and teaching; Ethnology -- Asia; Political science; Democracy; Asia -- Politics and government; Social sciences